1998
DOI: 10.1136/vr.143.11.310
|View full text |Cite
|
Sign up to set email alerts
|

Rate of decline of cefotaxime and ceftazidime in milk following intramammary administration to healthy and mastitic dairy cows

Abstract: CEFOTAXIME and ceftazidime are third-generation cephalosporins that are stable to 3-lactamases and have a wide antibacterial spectrum and low toxicity (O'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The effect of mastitis on drug elimination is a somewhat controversial subject. Higher concentrations of cefotaxime were found in milk of mastitic quarters but no difference was seen in the elimination of ceftazidime (Rule et al 1998), or higher concentrations occurred for polymyxin B in healthy quarters (Malvisi et al 1991).…”
Section: Introductionmentioning
confidence: 95%
“…The effect of mastitis on drug elimination is a somewhat controversial subject. Higher concentrations of cefotaxime were found in milk of mastitic quarters but no difference was seen in the elimination of ceftazidime (Rule et al 1998), or higher concentrations occurred for polymyxin B in healthy quarters (Malvisi et al 1991).…”
Section: Introductionmentioning
confidence: 95%
“…The values for ceftazidime concentrations in milk over time at 1 h and 12 h post-administration of the 1st dose of antibiotics in healthy and mastitic cows were high (1028.2 ± 723.1 and 30.5 ± 25.7 and 966.8 ± 278.0 and 131.3 ± 34.9 µg/m , respectively). The authors observed that ceftazidime administered by intramammary infusion to healthy and mastitic cows was distributed from treated to untreated quarters and the t1/2 and rate constant in milk were similar 17 . The drug had good distribution from treated to untreated quarters and the presence of residues was observed, so that milk destined for human consumption had to be discarded for at least 72 h 17 .…”
Section: Introductionmentioning
confidence: 96%
“…The authors observed that ceftazidime administered by intramammary infusion to healthy and mastitic cows was distributed from treated to untreated quarters and the t1/2 and rate constant in milk were similar 17 . The drug had good distribution from treated to untreated quarters and the presence of residues was observed, so that milk destined for human consumption had to be discarded for at least 72 h 17 . It has been observed that low protein binding resulted in ceftazidime penetration into the mammary gland.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…β-lactam antibiotics such as ceftiofur, a third-generation cephalosporin, are often used in dairy cattle for the treatment of mastitis or dry cow therapy ( Hallberg et al, 2006 ; Campos et al, 2021 ). When cephalosporins are applied intramammarily, they are mainly excreted through the urine and udder ( Wilson and Gilbert, 1986 ; Rule et al, 1998 ; Ray et al, 2014 ). Yet, ∼13% of the IMM-administered ceftiofur dose in lactating cows, which includes two doses of 125 mg per quarter given 12 h apart, is detectable in the feces 5–6 days post-treatment ( European Agency for the Evaluation of Medicinal Products, 2002 ).…”
Section: Introductionmentioning
confidence: 99%